2020
DOI: 10.1089/neu.2018.6149
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Behavior Testing in Animal Models of Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a leading cause of morbidity worldwide, with patients often suffering from consequences such as cognitive deficits, social abnormalities, anxiety, depression, pain, and motor dysfunction. Given that these impairments often have a significant impact on the patient's quality of life, a key aim of therapeutic intervention in TBI is to mitigate these effects. Translational strategies to develop such interventions have heavily featured animal models of TBI. To assess the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 345 publications
2
39
0
Order By: Relevance
“…This suggests that the effect of a single dose of meloxicam can preserve motor performance for longer than the duration of action of the drug [12-24 hours (49, 50)]. This acute phase protective effect was attributed to the neuroprotective effects of this NSAID medication, namely, reduction of inflammatory cytokines, free radical synthesis, and altering arachidonic acid metabolism (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). This same protective effect is not seen with buprenorphine, which correlates with a study performed by Santiago et al (36) that showed buprenorphine can be used for post-operative pain alleviation after spinal cord injury without affecting behavioral, physiological, or anatomical parameters in rats (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the effect of a single dose of meloxicam can preserve motor performance for longer than the duration of action of the drug [12-24 hours (49, 50)]. This acute phase protective effect was attributed to the neuroprotective effects of this NSAID medication, namely, reduction of inflammatory cytokines, free radical synthesis, and altering arachidonic acid metabolism (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). This same protective effect is not seen with buprenorphine, which correlates with a study performed by Santiago et al (36) that showed buprenorphine can be used for post-operative pain alleviation after spinal cord injury without affecting behavioral, physiological, or anatomical parameters in rats (36).…”
Section: Discussionmentioning
confidence: 99%
“…A rotating pole test was used to assess neurological motor dysfunction in the rats after bTBI, with and without pain medications ( 52 , 53 ). The rotating pole test was performed as described earlier ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sociability deficits occur in Service members with mTBI and in blast-exposed Veterans, preclinical studies addressing this issue are inconclusive ( 39 , 63 ). Shultz et al provides an overview of social interaction testing in the context of TBI, emphasizing the need for increased use of automated tracking capable of detecting social behaviors ( 64 ). Sociability in preclinical studies is measured by the duration of an animal's interaction with an unfamiliar animal of the same species.…”
Section: Translational Considerations Of Behavioral Impairmentsmentioning
confidence: 99%
“…FGF20 is also associated with 5-HT and depressive symptoms in adults [53]. Notably, some patients experience anhedonia and despair after TBI [54]. We speculated that FGF20 can ameliorate neurological deficits following TBI and that exogenous FGF20 can accelerate skull healing after TBI because of the important role of FGF20 in skull closure observed in developing mice [55].…”
Section: Tbimentioning
confidence: 97%